2020
DOI: 10.1111/1744-7917.12751
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of neuropeptides and their receptor genes in Bemisia tabaci and their transcript accumulation change in response to temperature stresses

Abstract: Insect neuropeptides play an important role in regulating physiological functions such as growth, development, behavior and reproduction. We identified temperaturesensitive neuropeptides and receptor genes of the cotton whitefly, Bemisia tabaci. We identified 38 neuropeptide precursor genes and 35 neuropeptide receptors and constructed a phylogenetic tree using additional data from other insects. As temperature adaptability enables B. tabaci to colonize a diversity of habitats, we performed quantitative polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…On the other hand, recently published study by Li et al (2020) showed significant decrease in capa expression level after 4 h of cold stress (4 • C) and no changes after 1 h, in Bemisia tabaci. Together with the changes in neuropeptide precursor level, decrease in expression level of CAPA receptor was also observed (Li et al, 2020). The Terhzez's group also showed that during recovery from cold stress, the mRNA level of leucokinins increases in Drosophila suzukii (Terhzaz et al, 2018).…”
Section: Neuropeptides Diuresismentioning
confidence: 78%
See 4 more Smart Citations
“…On the other hand, recently published study by Li et al (2020) showed significant decrease in capa expression level after 4 h of cold stress (4 • C) and no changes after 1 h, in Bemisia tabaci. Together with the changes in neuropeptide precursor level, decrease in expression level of CAPA receptor was also observed (Li et al, 2020). The Terhzez's group also showed that during recovery from cold stress, the mRNA level of leucokinins increases in Drosophila suzukii (Terhzaz et al, 2018).…”
Section: Neuropeptides Diuresismentioning
confidence: 78%
“…*The effect was observable during recovery time after cold stress in D. melanogaster and no effect was observed in B. tabaci during cold stress. ** Li et al (2020) showed decrease in capa level in B. tabaci after 4 h of cold stress, whereas Terhzaz et al (2015) a significant increase in D. melanogaster after 6 and 24 h of cold stress, the arrows represent an increase (↑) and a decrease (↓) in gene expression. n.e., no effect observed.…”
Section: Metabolismmentioning
confidence: 93%
See 3 more Smart Citations